Mapping of the X linked form of hyper IgM syndrome (HIGM1). Issue 3 (March 1993) - Padayachee, M; Levinsky, R J; Kinnon, C; Finn, A; McKeown, C; Feighery, C; Notarangelo, L D; Hendriks, R W; Read, A P; Malcolm, S
Abstract : X linked immunodeficiency with hyperimmunoglobulinaemia M (HIGM1), which is characterised by agammaglobulinaemia together with excess IgM production reflecting an impairment of the immunoglobulin heavy chain class switch of B lymphocytes, has been mapped to Xq26. We report multipoint linkage data in six families with HIGM1 which show that the most likely position for the gene is close to HPRT with a maximum lod score of 4.89. The finding of recombinations between HIGM1 and both HPRT and DXS42 implies that HIGM1 is not allelic to X linked lymphoproliferative disease. These data will be useful in genetic counselling in families and will also be useful in testing candidate genes.